Research on the impact of sports event image on tourism loyalty in heritage sites: An empirical study based on the Yongding Tulou marathon - Juan Du; Guifeng Zheng; Jingxuan Liang; Yongqiang Ma (PLoS ONE, 2025)
Heritage tourism related to sports events is widely recognized as a new paradigm of integration between culture, sports, and tourism. By combining sports events with world heritage sites, it attracts more tourists to pay attention to world heritage, serving as an important practice for the protection and sustainable development of world cultural heritage. However, the academic community still lacks discussions on its composition and impact effects. This study, based on the event of the 2022 Yongding Tulou Marathon in Fujian, constructs a multiple impact model of sports event events on tourist loyalty to heritage sites, integrating social and market perspectives. It follows the logic of “recognition-emotion-behavior” and uses PLS-SEM for empirical testing. PLS-MGA is conducted based on tourist demographic characteristics to explore the impact of different consumer group characteristics on the influencing paths. The results show: (1) The image of sports events is an important factor affecting tourist loyalty and the image of heritage sites, but it is difficult to directly influence tourists’ sense of place attachment; (2) The image of heritage is more deeply rooted in the heart, prompting tourists to develop loyalty and attachment to the heritage site, while attachment can also directly stimulate tourist loyalty; (3) The image of sports events can enhance the cognitive image of heritage through positive tourist experiences, thereby improving tourist loyalty to the heritage site. Additionally, the image of sports events can also stimulate tourists’ heritage image and sense of place attachment, ultimately strengthening loyalty to the heritage site; (4) Demographic variables such as gender, age, frequency of participation, and monthly running distance are key factors affecting the mechanism through which the image of sports events influences destination loyalty. The research findings not only reveal the theoretical process of how the image of event events influences multiple behaviors of tourists at heritage sites but also provide a comprehensive perspective and methodological tools for the study of sustainable development of world heritage sites. They also offer theoretical references for managers to effectively leverage the positive effects of developing sports tourism projects in heritage tourism destinations.